2017
DOI: 10.15376/biores.12.3.5031-5044
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cellulose Nanofibrils with Varying Chemical Compositions

Abstract: Cellulose nanofibrils (CNF) can be divided into lignocellulose nanofibrils (LCNF), holocellulose nanofibrils (HCNF), and pure cellulose nanofibrils (PCNF), dependent upon their chemical composition. The effect of the chemical composition on the defibrillation efficiency and the properties of the CNFs prepared by wet disk-milling was investigated using six different wood species. The defibrillation efficiency was improved when the lignin and hemicellulose was removed, and smaller fibers with diameters in the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…CNF can be obtained by mechanical treatment of wood with strong shear forces such as a grinder, fluidizer, and homogenizer. On the basis of chemical composition, CNF can be categorized as lignocellulose nanofibrils (LCNF) that contain both lignin and hemicellulose, holocellulose nanofibrils (HCNF) that contain only hemicellulose and no lignin, and pure cellulose nanofibrils (PCNF) that comprise only the cellulose component (Park et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…CNF can be obtained by mechanical treatment of wood with strong shear forces such as a grinder, fluidizer, and homogenizer. On the basis of chemical composition, CNF can be categorized as lignocellulose nanofibrils (LCNF) that contain both lignin and hemicellulose, holocellulose nanofibrils (HCNF) that contain only hemicellulose and no lignin, and pure cellulose nanofibrils (PCNF) that comprise only the cellulose component (Park et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of an aqueous medium during the mechanical isolation of NCs has also been gradually implemented to improve the delamination process. A recent study by Park et al [87], revealed enhanced defibrillation efficiency of wood-based microfibrils using a wet diskmilling process for the production of CNFs. Higher tensile strength of the subsequently prepared CNFs-based nanopapers was observed.…”
Section: Mechanical Isolation Of Ncsmentioning
confidence: 99%
“…Thus, the fabrication of a high-strength long filament from natural cellulose fiber, especially from cellulose nanofibril (CNF) [4,8,[17][18][19][20], is challenging. CNF can be generally isolated from plant cell walls by a mechanical defibrillation process, such as wet disk-milling (WDM), high-pressure homogenizing (HPH), and ball-milling [3,6,[21][22][23]. The CNF has been observed to be approximately 10-30 nm in diameter, with excellent properties such as large specific surface area, good thermal properties, and high strength [6,9,21,22].…”
Section: Introductionmentioning
confidence: 99%